COMPARISON OF CLINICAL OUTCOMES OF TYPE 2 DM PATIENTS WITH OVERWEIGHT AND OBESITY VERSUS THOSE WITH NORMAL BMI - Ng, Jennifer Lourdes; Pajimna, Janine Audrei; Encarnacion-Fernandez, Pajimna; Tappan, Sweet Garllie; Jasul Jr., Gabriel; Dampil , Oliver Allan (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES This study aimed to determine the difference in glycemic control, metabolic parameters (LDL, HDL, triglycerides, and blood pressure control) and the presence of retinopathy and/or nephropathy between overweight and obese versus normal body mass index (BMI) type 2 diabetes mellitus patients. METHODOLOGY This is an analytic cross-sectional study of type 2 diabetes mellitus patients from outpatient clinics at St. Luke’s Medical Center, Quezon City. Available medical records and laboratory tests were reviewed. Data were analyzed and compared between those overweight and obese versus those with normal BMI based on Asia Pacific Guidelines. RESULTS A total of 248 patients with type 2 diabetes mellitus were included in the study. Patients who are overweight and obese have a significantly higher risk of having uncontrolled diabetes (p=0.011), low HDL (p=0.035) and albuminuria (p=0.027) compared to those with normal BMI. There were no significant difference between overweight and obese patients versus those with normal BMI with regard to BP control, high LDL, high triglycerides and retinopathy. CONCLUSION Type 2 diabetes mellitus patients who are overweight and obese have a higher risk of developing uncontrolled diabetes, low HDL and albuminuria compared to those with normal BMI.